Maintenance management for energy conservation in office building / Nurul Farieda Reesha Anuar - Anuar, Nurul Farieda Reesha (Faculty of Architecture,Planning and Surveying, 2015)
Nowadays, energy conservation at office building are more been developed by government in matter of contribution to global warming and also cut cost. Energy conservation also believes reducing energy wastage that brings to energy conservation. In this research,researcher study on maintenance management for energy conservation in office building to know about the maintenance management work for energy conservation. Researcher wants to understand the principle and implementation of energy conservation in building, to identify the level of awareness among technical personal about energy conservation office, to assess or evaluate what needs to be emphasized in maintenance management for energy conservation and give recommendations to the maintenance management for energy conservation in office building. Through this research, maintenance management will be identified as a affected to the energy conservation and the awareness occupant about the energy conservation in office building. Primary and secondary data is carried out to finish this study. Primary and secondary is used to identify current status of energy conservation office building in Malaysia. Meanwhile,secondary data is used to identify the maintenance management work in energy conservation and measure the awareness among technical personal about energy conservation in energy conservation office building. In conclusion, maintenance management very important to energy conservation in office building. It is because when have good and complete maintenance for energy conservation, the concept for energy conservation will success. With this research, I get the maintenance management for energy conservation should have systematic maintenance and all building should have energy conservation concept in their building.